Complexing Properties of Synthesized 1,3,5-Triaza-7-Phosphaadamantane Derivatives Towards Some Lanthanides and Transition Metal Cations With Significant Antimicrobial and Antioxidant Activities - Lassaad Baklouti; Besma Mellah; Waleed S. Koko (SAGE Publishing, 2023)
The synthesis of new water-soluble N-alkylated derivatives of 1,3,5-triaza-7-phosphaadamantane is presented. Ru(PPh 3 ) 2 Cl 2 has been used to react with 1-(4-nitrobenzyl)-3,5-triaza-1-azonia-7-phosphaadamantane bromide (PTAR). By using elemental analysis, NMR, and IR spectroscopy, the obtained compounds were identified. The UV-visible absorption spectroscopy has been used to monitor the complexation of various transition metal cations. Studies on conductivity have been utilized to validate the complexes' stoichiometries. Using the disc diffusion method, five bacteria strains were used for the study of the antimicrobial activity of compounds 1-3 . All tested pathogens, including M luteus LB 141107, were found to have strong biologic activity against the compounds tested in this study. Additionally, DPPH (2,2-diphenyl-1-picrylhydrazyl) has been tested for its ability to scavenge hydrogen peroxide and free radicals. According to our results, these compounds exhibit excellent radical scavenging properties.